Searches Shale Oil in Western Siberia; SGEM. 16th International Multidisciplinary Scientific GeoConference; Bk. 1, vol. 3 - Lobova G. A. Galina Anatolyevna; Isaev V. I. Valery Ivanovich; Fomin A. N. Aleksandr Nikolaevich; Stotsky V. V. Vitaly Valerjevich (Oil and gas exploration, 2016)
Title screen